Multiscale Strategic Planning Model for the Design of Integrated Ethanol and Gasoline Supply Chain - Andersen, Federico Ezequiel (2013)
The design and planning of an integrated ethanol and gasoline supply chain is addressed, and is composed of harvest-ing and production sites for ethanol, petroleum reﬁneries, distribution centers where blending takes place, and the retail gas stations where blends of gasoline and ethanol are sold. We postulate a superstructure that combines all the compo-nents of the supply chain and different means of transportation, and model this multiscale design problem as a multiper-iod MILP model. In order to identify regions where investments are needed and the optimal conﬁguration of the network, a strategic planning model is considered in which gasoline stations are aggregated in different regions. A detailed formulation is considered where regions are disaggregated into gas stations to determine the retroﬁt projects for the selection of blending pumps over their expected life. Also, the application of these MILP models with two large-scale problems are illustrated.